Comparison of robotic‐assisted versus conventional unicompartmental knee arthroplasty for the treatment of single compartment knee osteoarthritis: A meta‐analysis. Issue 1 (24th September 2020) - Zhang, Pei; Xu, Keteng; Zhang, Jiale; Chen, Pengtao; Fang, Yongchao; Wang, Jingcheng
Abstract: Background: The robotic‐assisted unicompartmental knee arthroplasty (UKA) is proposed to improve the accuracy of component positioning. Methods: We conducted a literature search in Medline, Embase, Web of Science and the Cochrane Library until April 2020. Results: Our meta‐analysis included 10 articles, involving 1231 knees. Our meta‐analysis demonstrated that the robotic group had significantly better results in outliers of limb alignment ( p < 0.001) and outliers of tibial alignment ( p < 0.001). No statistical differences were found in the American Knee Society Score ( p = 0.63), range of motion ( p = 0.93), pain ( p = 0.27), rate of revisions ( p = 0.73) and rate of complications ( p = 0.67). Conclusions: Robotic‐assisted UKA has better component position accuracy compared with conventional UKA. But there was no significant difference in clinical results. In order to further evaluate the utility of robotic‐assisted UKA, long‐term follow‐up randomized controlled trials (RCTs) are needed, as well as studies to evaluate the correlation between postoperative alignment and long‐term clinical results.